Repeat exercise renograms in hypertension identify persistent renal dysfunction - Clorius, John Henry; Hupp, Thomas; Mandelbaum, Alexander; Schmölder, Henning; Kaick, Gerhard van (Journal of hypertension, 1995)
Background - Hypertensives may develop bilateral trapping of para-aminohippurate analogues in the tissue of the kidneys during light exercise, as can be demonstrated using radioactively labelled [131l]-hippurate or [99mTc]-mercaptoacetyl-triglycine. Tracer accumulation in the kidneys during exercise results in a typical renographic pattern, the bilateral-abnormal exercise renogram. The disturbance is common during exercise, being found in almost 60% of all hypertensives, regardless of aetiology. - Objective - To determine whether bilateral-abnormal exercise renograms are spurious phenomena, or whether the results of exercise renography are reproducible. - Design - We reviewed the renographic examinations of 27 hypertensive patients, each of whom had undergone at least one resting and two [131l]-hippurate or [99mTc]-mercaptoacetyl-triglycine γ-camera exercise renograms. The status of the renal artery at the time of scintigraphy was documented, using available arteriograms. The causes of vascular lesions were noted, as were revascularization procedures and the antihypertensive medication being taken at the time of scintigraphy. - Results - The average time between exercise renograms was 15.5 months, and 24 of the 27 hypertensive patients had comparable results in the first and the follow-up exercise renogram, divergent results being noted for the other three patients. Re-evaluation of the scintigrams of the three hypertensive patients with divergent results suggested that intermittent pelvic retention might have caused errors of interpretation in two. We found it notable that neither revascularization nor a change in antihypertensive drug therapy influenced the results of exercise renography. Exercise renograms were reproducible over long periods, and potential extraneous influences on blood flow, such as antihypertensive drugs or revascularization, failed to alter the results. - Conclusion - The results are considered relevant, because a direct relationship appears probable between hypertension and the disturbance investigated. Reproducible results suggest that the exercise-mediated disturbance is fixed to the kidneys, that it can be reactivated repeatedly and that it may play a role in maintaining hypertension.
Gesehen am 19.11.2025